Improved Interpretation of Deep Seismic Reflection Data in Areas of Complex Geology Through Integration With Passive Seismic Data Sets. Issue 12 (21st December 2018) - Dentith, Michael; Yuan, Huaiyu; Murdie, Ruth Elaine; Pina‐Varas, Perla; Johnson, Simon P.; Gessner, Klaus; Korhonen, Fawna J.
Abstract: The Capricorn Orogen records the Paleoproterozoic amalgamation of the West Australian Craton. 2‐D deep‐seismic reflection data across the Orogen are difficult to interpret due to the complex geology, and fundamental questions remain about the nature of the basement in the northern part of the Orogen. Passive seismic data have been collected along a 250‐km‐long transect across the central part of the Capricorn Orogen. The passive seismic recordings utilized teleseismic arrivals to construct a velocity section using the receiver function common conversion point method and to estimate crustal thickness and V p / V s using the H ‐ k method. A shear velocity cross section was created using ambient noise‐based methods. An integrated interpretation of all the seismic data sets shows that basement in the central Capricorn Orogen comprises a series of distinct terranes. These are recognized based on changes in crustal reflectivity, velocity and V p / V s . We interpret these terranes as originating from an island arc caught in the collision between the Glenburgh Terrane and the Pilbara Craton as part of the 2215–2145 Ma Ophthalmia Orogeny. Although passive seismic data do not have the resolution of reflection data, the information gained from the passive data places important constraints on the reflection interpretation and provides complementary information about changes in crustal composition. We propose that passive seismic data represent a cost‐effective complementary geophysical data set that can greatly assist with the interpretation of deep reflection sections in areas of complex geology. Key Points: Deep reflection data in areas of complex geology can be very hard to interpret Teleseismic and ambient noise data are relatively cheap to acquire and provide information complementary to the reflection data We present an example where an existing reflection interpretation was modified and improved by working with both kinds of data together